Volumetric spatiotemporal data model - Mohd. Rahim, Mohd. Shafry; Mohamaed Shariff, Abdul Rashid; Alias, Mohammad Ashari (Springer Berlin Heidelberg, 2007)
This paper summarizes the Volumetric Spatiotemporal Data Model which has been developed to manage surface movement in the Virtual Geographical Information Systems (VGIS). Volumetric is one type of spatial object in the VGIS, which is used to develop visualize 3D information. In order to develop real process in VGIS, temporal element is an important issue to integrate with 3D object. Here, we propose one spatiotemporal data model used to manage volumetric surface movement according to movement criteria used in VGIS. Time has been integrated with the data model and temporal version of volumetric surface data can be stored by using the model. This model has been implemented by developing prototype of visualization system using Triangulation Irregular Network (TIN) with integrated time in the TIN structure. Result shows that the data model which has been proposed can work with a visualization algorithm using linear interpolation and improvement TIN structure.